Employers’ Perspective Towards People with Disabilities: A Review of The Literature - Heera, Sonali; Devi, Arti (The South East Asian Journal of Management, 2016)
The significance of employment for people with disabilities has gained interest among researchers. The successful inclusion of people with disabilities in the employment settings depends on the employers’ perspective towards their integration in the mainstream workforce. This review examines literature over the past 25 years with an attempt to assess the employers’ perspective and specifically, the factors influencing their perspective towards inclusion of people with disabilities in employment. A search of electronic databases has resulted in the selection and analysis of 44 articles. The literature indicates that employers’ perspective plays an important role in providing and maintaining employment opportunities for people with disabilities. A number of factors including type of disability and demographic variables affecting employers’ perspective have been identified and discussed.